Pengaruh Perubahan Iklim Terhadap Kedalaman dan Intensitas Hujan - Yasa, I.W.; Sulistiyono, H.; Hartana, H.; Jayanegara, I.D.G.; Saidah, H.; Saadi, Y.; Agastya, D.M. (Tadulako University, 2024)
Climate change is a natural phenomenon where there is a very extreme change in the value of climatological elements. The increase in floods and droughts is caused by changes in the characteristics of rain that are far below normal. This study aims to determine the trend of climate change resulting in changes in the characteristics of rain, namely the depth and intensity of rain. Assessment of climate change is seen from trend graphs and the Mann-Kendall statistical test to determine significant changes. To determine the effect of climate change on the characteristics, of rainfall, the calculation is divided into 3 periods, namely period 1 (1994-2003), period 2 (2004-2014), and period 3 (2014-2018). Based on the Mann-Kendall statistical test, climate change also occurred as indicated by a significant Z value, namely the Kediri and Sopak climatological stations 4.64 and 6.26, respectively. The pattern of changes in the daily average rain depth and intensity has occurred from 1994 – 2018 where in period 1 in 1994-2003 there was a normal trend, in period 2 in 2004-2013 there was an increasing trend and in period 3 in 2014-2018, there was an extreme increasing trend